Assessment of Functioning in Older Adults Hospitalized in Long-Term Care in Portugal: Analysis of a Big Data - Ramos, Ana; Fonseca, César; Pinho, Lara; Lopes, Manuel; Brites, Rui; Henriques, Adriana (Frontiers in Medicine, 2022)
Background Functioning assessment is a key tool for health professionals to characterize the person's degree of dependence and plan care. Objectives The objectives were: (1) know the functioning components of older adults hospitalized in the National Network of Continuous Integrated Health Care (NNCIHC) in Portugal; and (2) compare the conceptual frameworks used in this network with the International Classification of Functioning, Disability and Health (ICF). Methods A longitudinal retrospective study is made with 171,414 individuals aged 65 years and over. The Principal Components Analysis (PCA) was realized to reduce the number of variables, previously suggested by a scoping review, about the concepts that characterize the functionality. Then, a consensus meeting was held, where the items were matched with the ICF. Results The average age of the sample is 80.17 years old (SD = 7.383), predominantly female (59%), without a spouse (54%), and with <6 years of education (56.4%). Four concepts were grouped: mobility, life daily activities, instrumental activities, and cognitive status that demonstrated good internal consistency. Most items correspond to ICF, except for the item “taking medication.” Conclusion Theoretical and conceptual similarities support the use of instruments based on the ICF in Portugal's healthcare network. We suggest that ICF also encompasses a specific dimension related to medication management, given its importance for people's health.